2000
DOI: 10.1038/sj.gt.3301059
|View full text |Cite
|
Sign up to set email alerts
|

Type I consensus interferon (CIFN) gene transfer into human melanoma cells up-regulates p53 and enhances cisplatin-induced apoptosis: implications for new therapeutic strategies with IFN-alpha

Abstract: In this study, we describe the effects produced by the retroviral transduction of human type I consensus IFN (CIFN) coding sequence into the 8863 and 1B6 human melanoma cell lines, derived from a metastatic and a primary human melanoma, respectively. Melanoma cell lines producing approximately 10 3 IU/ml of IFN were obtained. Interestingly, cisplatin treatment of IFN-producing 8863 and 1B6 melanoma cells resulted in a three-to four-fold increase in the percentage of apoptotic cells with respect to similarly tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…20 We have recently shown that the retroviral transduction of human consensus IFN (CIFN) coding sequence into two human melanoma cell lines resulted in a strong augmentation of cisplatin-induced apoptosis, associated with an IFN-dependent increase in p53 expression. 22 Similar effects, although less marked, were also observed after cultivation of parental melanoma cells in the presence of exogenous IFN. Cisplatin administration to nude mice bearing IFN-producing tumors resulted in complete tumor regression, whereas only partial tumor inhibition was observed after cisplatin treatment of mice with control tumors.…”
supporting
confidence: 57%
See 4 more Smart Citations
“…20 We have recently shown that the retroviral transduction of human consensus IFN (CIFN) coding sequence into two human melanoma cell lines resulted in a strong augmentation of cisplatin-induced apoptosis, associated with an IFN-dependent increase in p53 expression. 22 Similar effects, although less marked, were also observed after cultivation of parental melanoma cells in the presence of exogenous IFN. Cisplatin administration to nude mice bearing IFN-producing tumors resulted in complete tumor regression, whereas only partial tumor inhibition was observed after cisplatin treatment of mice with control tumors.…”
supporting
confidence: 57%
“…22 The 1B6 clone was isolated from the M10538 cell line, established from a primary skin melanoma lesion, 27 whereas the 8863 cell line was derived from a metastatic melanoma. 28 The HLA haplotype of the two patients was previously identified.…”
Section: Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations